2019
DOI: 10.1002/art.40789
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Opioid Use in Rheumatoid Arthritis: Prevalence and Predictors

Abstract: Objective. The opioid epidemic is a major public health concern. However, little is known about opioid use among rheumatoid arthritis (RA) patients. We undertook this study to examine trends in chronic opioid use in RA patients in 2002-2015 and to identify clinical predictors.Methods. RA patients were identified from the Corrona registry. Opioid use was ascertained from surveys obtained at clinical visits as often as every 3 months. Chronic opioid use was defined as any opioid use reported during ≥2 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 32 publications
7
60
1
Order By: Relevance
“…In a cohort study conducted in the US in 2002-2015, the criterion of chronic opioid use was defined on the basis of documented opioid use during at least two follow-up visits, with the median time between two visits being 156 days. In the study group, the percentage of chronic opioid users more than doubled from 7.4 in 2002 to 16.9 in 2015 21 . Another study found that patients with RA in 2014 were 1.5 times more likely to use opioids than those without RA (40 % vs 24%) and were almost twice as likely to use opioids chronically (12% in RA vs 4% in non-RA patients, the rate index was adjusted for age and gender), with the study assuming that chronic opioid use was considered to be providing the patient with a prescription for 60 days or longer 3 .…”
Section: Changes In Opioids Usementioning
confidence: 90%
See 4 more Smart Citations
“…In a cohort study conducted in the US in 2002-2015, the criterion of chronic opioid use was defined on the basis of documented opioid use during at least two follow-up visits, with the median time between two visits being 156 days. In the study group, the percentage of chronic opioid users more than doubled from 7.4 in 2002 to 16.9 in 2015 21 . Another study found that patients with RA in 2014 were 1.5 times more likely to use opioids than those without RA (40 % vs 24%) and were almost twice as likely to use opioids chronically (12% in RA vs 4% in non-RA patients, the rate index was adjusted for age and gender), with the study assuming that chronic opioid use was considered to be providing the patient with a prescription for 60 days or longer 3 .…”
Section: Changes In Opioids Usementioning
confidence: 90%
“…The cohort studies also highlighted the medications that RA patients used concomitantly with chronic opioids. In one of the studies slightly more than 40% of respondents took biological DMARDs, 27% took glucocorticosteroids and almost 18% took antidepressants 21 . To this list other studies add the frequent use of benzodiazepines, antiepileptic drugs 26 and the use of non-opioid analgesics such as acetaminophen or NSAIDs 28 .…”
Section: Opioids and Rheumatoid Arthritismentioning
confidence: 99%
See 3 more Smart Citations